UJI KINERJA PENJEMURAN GABAH PADA PARA-PARA MEKANIS DENGAN TIGA KONDISI LINGKUNGAN - Setiawan, Mahendra Dwi; ., Tamrin; Lanya, Budianto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
Traditional grain drying is a practical way of drying grain, cheap, simple and commonly used by farmers.  Grain is spread on the floor which causes grain mixed rock and dirt around the drying floor.  Disadvantages in traditional grain drying are it requires a lot of manpower to spread, to flip back and to collect the grain, and requires large floor for drying.  On the other hand, grain drying using mechanical rack has the advantage that it avoids some of the grain that is not mixed with rock and dirt while drying, shorten the drying time, and easily move the grain when it rains. The purpose of this study was to test the performance of mechanical dryer.  The experiments were set up with drying treatment at 80 cm above the surface of the cement floor, on top of grassy land surface, and on the surface of rocky land with 4 cm thick of sample. The parameters measured in this study were consisted of drying time, moisture content, drying rate, energy of radiation received, the energy to evaporate the water and heats of the material, and drying efficiency. The results of research on the treatment of three environmental conditions indicated that. The average water content was 13.90% wb, 13.82% wb, and 13.98% wb respectively for the surface of the cement floor, on top of grassy land surface, and on the surface of rocky land. The average drying rates in this study were 0.494% /h for the surface of cement floor, 0.487% /h for on top of grassy land surface, and 0.534% /h for on the surface of rocky land.  Drying time in this study were 10 - 11 hours with an average radiation energy received on this experiment at 614.42 Watt/m2. Drying efficiency of each treatment were 12.58%, 12.43%, and 13.72% respectively for the surface of the cement floor, on top of grassy land surface, and on the surface of rocky land. From the observations and calculations derived drying over the surface of cement floor, on top of grassy land surface, and on the surface of rocky land are recommended for drying using a mechanical rack dryer. Keywords: Drying, grain, mechanical rack